Edukasi Pengelolaan Stres Untuk Penyitas Kanker Dan Keluarga Anggota Komunitas Think Survive Kota Makassar - Asrina, Andi; Idris, Fairus Prihatin; Widyastuti, Nur Sri; Annisa, Nurul (Wal'afiat Hospital Journal, 2022)
Cancer is a cell disease characterized by uncontrolled cell proliferation. Cancer is also often called a malignant tumor. People in many nations often think of cancer as an incurable disease, a disease that causes death and is more often experienced by older adults. According to the community's general chairman, several factors cause many cancer survivors to experience stress. The purpose of this activity is to increase the knowledge of cancer patients. Stress Management for Cancer Survivors and Families. The method used in this activity is counseling or delivering material via online (zoom). The results of the activities achieved are the level of knowledge of cancer survivors before being given counseling materials. There are 7 cancer patients (58.33%) and a good level of knowledge there are 5 people (41.66) based on the level of sufficient knowledge. the level of knowledge of the community after the counseling increased slightly, namely, the level of knowledge was sufficient there were 5 people (41.66). and an increase in the level of good knowledge of 7 people (58.33%). Conclusion After counseling, it was concluded that cancer survivors had a good level of knowledge after counseling about stress management for cancer survivors and their families. Bringing in professionals in the psychological field to provide information, education, and support to cancer survivors who are members of the Think Survive community.